تطوير موقع تسيير ومراقبة حظيرة مركبات - - أيمن كروش - هزله هارون (university of eloued جامعة الوادي, 2024)
لهدف من مشروعنا الوارد في هذا التقرير هو تصميم وتنفيذ بسيط ومحسن لتسيير ومراقبة حضيرة السيارات وقد أجريت عملية الإنجاز من خلال ثالثة مراحل وهي: أولا قمنا بدراسة وجمع المعلومات والإحصائيات المختلفة لخدمة التسيير والمراقبة لحظيرة المركبات، ثم المرحلة الثانية المتمثلة في النمذجة والتي قمنا فيها بوصف بأجزاء ومكونات الموقع باللغة الموحدة للنمذجة UML، أما المرحلة الأخيرة اعتمدنا في تطوير هذا الموقع على العديد من التقنيات: • قواعد بيانات MYSQL لتخزين البيانات • لغة ال PHP للتعامل مع قواعد بيانات / REACT / BOOTSTAP لإنشاء واجهة تفاعلية حديثة The objective of our project, as outlined in this report, is to design and implement a simple and optimized system for managing and monitoring a vehicle fleet. The project was carried out in three phases: First, we conducted a study and gathered various data and statistics relevant to the management and monitoring of vehicle fleets. The second phase involved modeling, during which we described the components and parts of the site using the Unified Modeling Language (UML). In the final phase, we developed the site using several technologies: • MYSQL databases for data storage • PHP language for database interaction • REACT/BOOTSTRAP for creating a modern, interactive interface.
مدكرة ليسانس اعلام الي
Keywords: حظيرة مركبات، صيانة، سائق.; vehicle fleet; maintenance; driver